HIV-related enacted stigma and increase frequency of depressive symptoms among Thai and Cambodian adolescents and young adults with perinatal HIV. (March 2021) - Aurpibul, Linda; Sophonphan, Jiratchaya; Malee, Kathleen; Kerr, Stephen J; Sun, Ly Penh; Ounchanum, Pradthana; Kosalaraksa, Pope; Ngampiyaskul, Chaiwat; Kanjanavanit, Suparat; Chettra, Kea; Suwanlerk, Tulathip; Mellins, Claude A; et al.
HIV-related enacted stigma and social problems may increase risk for depression and/or behavioral problems among adolescents and young adults with perinatal HIV(AYA-PHIV), yet few studies have explored stigma in AYA-PHIV residing in low-to-middle income regions, including Southeast Asia. We assessed HIV-related enacted stigma and social problems in AYA-PHIV who participated in the RESILIENCE study (clinicaltrials.gov identification: U19AI53741) in Thailand and Cambodia using specific questions during structured in-person interviews. Depression was measured by the Child Depression Inventory for children <15 years, or the Center for Epidemiologic Studies Depression Scales for youth ≥15 years); behavioral problems were measured by the Child Behavior Checklist (CBCL-caregiver report). Among 195 AYA-PHIV (median age 16.9 years), 25.6% reported a lifetime experience of enacted stigma, while 10.8% experienced social problems due to HIV infection. The frequency of depressive symptoms was nearly two-fold higher among AYA-PHIV with compared to those without HIV-related enacted stigma (34.7% vs. 16.0%, p = 0.005). Caregiver-reported behavioral problems were detected in 14.6% of all AYA-PHIV, with no differences between those with and without HIV-related enacted stigma. Low household income and caregiver mental health problems were independent risk factors for depressive symptoms; HIV-related enacted stigma was also associated with increased risk, warranting targeted services to support AYA-PHIV.